Effect of Taxpayer Data and Information Confidentiality Principle on Tax Amnesty Against Law Enforcement in Indonesia - Ratih Damayanti (Unnes Law Journal, 2019)
The principle of confidentiality in the Tax Amnesty can have a negative impact, the impact of which may occur frauds by individual taxpayers and tax officials. If there is fraud, the process of investigation and investigation to find evidence will be difficult. Law enforcement agencies and examining bodies such as the KPK, BPK, and other related agencies will have difficulties and will not be able to break through taxpayer assets or data because these assets and data are private and protected by law. This can hamper the law enforcement process, especially law enforcement in the tax sector. The principle of confidentiality in Tax Amnesty has an effect on law enforcement. The principle of confidentiality in Tax Amnesty provides potential moral hazard. A moral hazard occurs because of the opportunities or opportunities that enable these actions to materialize. Opportunities for Fiscus and Taxpayers to meet in person. This has the potential to cause a gray area between the Taxpayer and the Fiscus which can cause moral hazard to the Taxpayer. The authority of the Fiscus is prone to be misused, so that it can lead to several criminal actions that can be carried out, namely embezzlement or corruption that can harm the country's finances. And when the crime occurs at a Tax Amnesty Taxpayer, it will be difficult to enforce the law because the data and information sourced from the Declaration and its attachments cannot be used as a basis for investigation, investigation, and / or criminal prosecution of the Taxpayer cannot be used as a taxpayer basis for investigation, investigation and / or criminal prosecution of taxpayers.